2018
DOI: 10.1021/acsaem.8b01336
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a Cobalt Carbide (Co3C) Oxygen Evolution Precatalyst

Abstract: We report on the fabrication of cobalt carbide (Co 3 C) particles via a wet-chemical synthetic procedure and also describe their electrochemical oxidation to amorphous Co oxide particles that can be used as oxygen evolution reaction (OER) catalysts. Metal chalcogenide, carbide, and pnictide materials have been investigated recently, but there is some controversy regarding the composition of the actual electrocatalytic material. Carbides, in particular, have not been heavily studied as OER catalysts, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
145
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(151 citation statements)
references
References 30 publications
5
145
1
Order By: Relevance
“…Mullin's group recently reported the application of cobalt carbide (Co 3 C) for the OER in alkaline solution . It was demonstrated that under electrochemical OER conditions, the Co 3 C particles were fully converted to amorphous cobalt oxide.…”
Section: Cobalt and Nickel Containing Non‐metal And Metalloid Elementmentioning
confidence: 99%
See 3 more Smart Citations
“…Mullin's group recently reported the application of cobalt carbide (Co 3 C) for the OER in alkaline solution . It was demonstrated that under electrochemical OER conditions, the Co 3 C particles were fully converted to amorphous cobalt oxide.…”
Section: Cobalt and Nickel Containing Non‐metal And Metalloid Elementmentioning
confidence: 99%
“…1.0–1.9 V vs RHE) for the Co 3 C sample. Taken from with permission of the American Chemical Society.…”
Section: Cobalt and Nickel Containing Non‐metal And Metalloid Elementmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the outstanding OER on cobalt pnictides, it is currently argued that the in‐situ evolution of cobalt oxides/(oxy)hydroxides on the surface of cobalt pnictides during OER is a dominant factor for enhancing the catalytic activity. [ 10–14 ] Zhu et al and Li et al have both reported that the high OER activity of CoP nanocrystal results from the significant transition of Co 2+ states to higher oxidation states and the formation of Co oxides/hydroxides during the anodic reaction process. [ 9,15 ] Meanwhile, Fan's group has found that the active CoOOH layer exists in the CoN surface prior to the OER process, and is further oxidized in the OER process to produce the CoO 2 /Co x N, which is a more efficient species for OER.…”
Section: Introductionmentioning
confidence: 99%